The participation of households in recycling among the lower income group : a case in Taman Jaya Diri residential / Gladius Marinus and Eddie Osong - Marinus, Cladius; Osong, Eddie (2014)
The Malaysia national target in recycling is to achieve 22% by the year of 2020. In fact, the current (2012) recycling rate in Malaysia is around 10.5% as stated by National Solid Waste Management Department. Due to this, the study to determine the level of participation in recycling as well as to analyze the factors associated with the level of participation was done. A total of 120 questionnaires were self distributed to households in Taman Jaya Diri Residential area. In the questionnaire, the respondents were asked about their profiles, and the assessment question of participation level and factor that lead them to recycle which includes the effective recycle facilities, concern about the environment and social pressure. The results show that the level of participation in recycling among the households is in the moderate level. The study also shows the factors associated with the level of awareness.